Direct conversion of chitin derived N-acetyl-D-glucosamine into 3-acetamido-5-acetylfuran in deep eutectic solvents. (February 2023) - Wang, Kai; Xiao, Yunfei; Wu, Changchun; Feng, Yimo; Liu, Zhipeng; Zhu, Xi; Zang, Hongjun
Abstract: 3-Acetylamino-5-acetylfuran (3A5AF) is an important nitrogen-containing fine chemical with broad application prospects and high research value. Herein, we report a novel method for the conversion of N-acetyl-d -glucosamine (NAG) to 3A5AF in the choline chloride-based deep eutectic solvents (DESs). The catalytic activities of various DESs have been smoothly screened, and DES 2 (choline chloride/PEG-200/boronic acid = 1/1/0.5) displayed the best catalytic performance. In the absence of any additional solvent, catalyst and additive, product 3A5AF was obtained in 18.3% yield after reacting at 180 °C for 15 min under atmospheric condition. In addition, DES 2 showed a good reusability. The possible reaction pathway was elucidated on the basis of the results of LC-MS and 13 C NMR spectra. This study provided a new perspective for the application of DES in the conversion of chitin biomass. Graphical abstract: Image 1 Highlights: Direct conversion of NAG to 3A5AF in DESs without any additional solvent, catalyst and additive was realized. 3A5AF was obtained in 18.3% yield at 180 °C in a period of 15 min under normal atmospheric conditions. The possible reaction pathways were proposed.